Uji Efektivitas Ekstrak Etanol Daun Sambung Nyawa (Gynura Procumbens (Lour) Merr.) Sebagai Antidiabetes Terhadap Tikus Putih Jantan (Rattus Norvegicus) Yang Diinduksi Aloksan - Destin Putri Lestari Zebua; Meldawati; Elfia Neswita; As-sirri Mirrian Farsya (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Longevity spinach leaf (Gynura procumbens (Lour) Merr.) is a traditional plant that contains various secondary metabolite compounds such as alkaloids, flavonoids, tannins and saponins, where flavonoids have various properties, including in the treatment of degenerative diseases such as diabetes mellitus. The purpose, of the research was to determine the effectiveness of the ethanol extract of Longevity spinach (Gynura procumbens (Lour) Merr.) leaf on reducing blood sugar levels in male white rats (rattus norvegicus) induced by alloxan. In this study, 5 test groups were used, namely negative control group, positive control group (metformin 9 mg), first dose 7.2 mg, second dose 14.4 mg, and third dose 21.6 mg. The rats were acclimatized and fasted before being given treatment, then their blood sugar was checked, before and after being induced by alloxan, then they were given treatment for 5 consecutive days and their blood sugar levels were checked once a day. The results of research from testing the ethanol extract of Longevity spinach leaf on male white rats proved effective in reducing blood sugar levels with the best dose, namely the 3rd dose (21.6 mg) on ​​the 6th day.